IMPLEMENTATION OF A MANAGEMENT INFORMATION SYSTEM (SIM) TO IMPROVE EMPLOYEE PERFORMANCE IN THE COMPANY - Arnesha Febra Syavera; Reno Fandika; Hadi Supratikta (PT. Jurnal Center Indonesia Publisher, 2024)
This research is to analyze the implementation of management information system to improve employee performance in the company. The method used is qualitative descriptive method of analysis. The data sources used are various references or library sources about the study of the implementation of management information systems to improve employee performance. Data collection techniques through documentation techniques, namely by carefully and critically reading various references. The result of this study is that the implementation of management information system provides benefits for employees by providing time efficiency, data accuracy, work effectiveness and group management that it can improve employee performance in the company.